Treatment Strategies of an Iris Implantation Cyst: A Case Report - Zarwan, Jessica; Maulidinia, Ayang Rashelda; Siregar, Astrid Mariam Khairani; Widyawati, Syska; Martha, Faraby; Rhendy, Rio (Majalah Oftalmologi Indonesia, 2025)
Introduction: Iris cyst can be divided into primary and secondary, both originating from epithelial cells. Although rare, the entity has a high recurrence rate. This clinical case report highlights the treatment strategies to treat and prevent the recurrency of iris cyst. Case Report: We report a rare presentation of a secondary iris cyst in a 20-year-old male with a history of cataract surgery 17 years prior. The patient underwent fine-needle aspiration and intracystic alcohol injection. However, the iris cyst recurred eight months after the procedure. Afterward, the invasive strategy of iris cyst excision was conducted. Eight months after the secondary iris cyst surgery, the patient showed no signs of recurrence. Discussion: Iris cyst is known to have a high recurrence rate, however, a minimally invasive treatment is still preferred, supported by previous studies showing no recurrence in treatment with fine-needle aspiration and intracystic alcohol injection. In our case, the iris cyst relapsed eight months after this procedure, warranting for surgical excision. Eight months after the excision, the patient showed no signs of recurrence. Conclusion: Although the recurrency of iris cyst is high, the authors suggest starting with non-invasive treatment with follow-up ensuring no recurrence before opting for a more invasive treatment.